Implementation of OFDM-RoF at 60 GHz with DCF for Long Haul Communication - Rashid, M. F.; Qamar, F.; Rashid, F.; Ahmad, S. (The Nucleus, 2016)
In this paper, a new design of optical system is proposed and analyzed which combine coherent OFDM with radio over fiber (RoF) for achieving data rate of 40 Gbps over 150 km Single Mode Fiber (SMF). Optical heterodyne method is used for generation of 60 GHz Millimeter wave. The transmitted RF signal through optical fiber using RoF method is degraded and to compensate it, post compensation scheme of Dispersion Compensating Fiber (DCF) is used. Constellation diagram has been observed after 150 km with and without DCF for performances evaluation of OFDM RoF system. The BER at receiver end is evaluated and from the results it can be concluded that the transmission distance and data rate has been increased